Individual Readiness for Change as Mediator between Transformational Leadership and Commitment Affective to Change - Nadhila Nuhanisa Radian; Wustari L. Mangundjaya (Departemen Teknik Sipil ITS, 2019)
Ministry of Public Works and Publich Housing (Ministry of PWPH) is currently in change process, due to president’s regulation regarding beucratic reform (birokrasi reformasi). This research aims to investigate ministry’s readiness for change and how transformational leadership style affect employee’s commitment to change in minisitry of PWPH. Organizational success during change implementation is strongly influenced by employees’ commitment to change, particularly affective commitment to change (AC2C). However, employees’ affective commitment to change is very dependent with individual readiness for change (IRFC), as IRFC indicates employees’ openness and acceptance towards change. Previous studies showed IRFC is influenced by leadership style, particularly transformational leadership (TL). This study aimed to gain insight the relationship between TL, IRFC and AC2C. This research was conducted in ministry of PWPH in Indonesia that is currently under a change process. With 177 respondents, result showed that TL significantly influences IRFC, which then affects AC2C. This finding emphasize role of leadership towards development of IRFC in employees to successfully implement change in organization.